China’s Landmass and Maritime Relations on the Edges: The Implications of Russia-Ukraine Conflict on the Cases of Kazakhstan and the Philippines - Aliya Peleo; Hugo Tierny (Contemporary Chinese Political Economy and Strategic Relations: An International Journal, 2022)
Among the persistent effects of the Cold War are the concerns that militarized conflicts are likely to occur at the frontiers of the former Cold War powers, and also that countries at these frontiers will inevitably sustain collateral damage regardless of their geostrategic alignment. On the western side of the Eurasian landmass, the armed conflict between Russia and Ukraine is conjoined to disputes over the limits of Russian and European political and economic influence. On the eastern side, economic disputes between the People’s Republic of China and the United States of America will, if militarized, have severe consequences for the US-aligned governments particularly at the Eastern periphery of China. Kazakhstan, which is at the geostrategic gap between Russia and China, continues to play a significant role in Russian and Chinese engagements with Europe. The Philippines has not diminished in value as leveraging-point for the US, most recently against China because of South China Sea dispute. Notwithstanding the militarization on the western front with Russia, the possibility of a militarized conflict with China may yet be mitigated if its interests in the North-Western Eurasian landmass are distinguished from its geopolitical goals in its maritime Southern periphery. This paper revisits the “guns or butter” metaphor, which was developed during the Cold war to describe the opportunity cost calculations, particularly of peripheral states such as Kazakhstan and the Philippines, regarding “security” vs. “socio-economic development”. The recent Belt and Road Initiative of China has highlighted the provision of Chinese development “butter” to its periphery, in contrast to the post-Cold War security “guns” provided for Kazakhstan by Russia through CSTO military alliance, and for Philippines by Mutual Defense Treaty with the US. If Russia and the United States fail to assure Kazakhstan and the Philippines, respectively, that military security relations remain recognizable and reliable, then China, either by invitation or hegemonic expansion, may choose to become more prominent in security-related issues in these countries. Within their respective territories, does Kazakhstan and the Philippines have the skill and resources to balance or moderate the geopolitical interests of these great-power states? Or will Central Asians and Southeast Asians have no choice but to take sides if Chinese, American, and European military forces are deployed in their respective regions?